SIMILE & METAPHOR IN TRANSLATION: A STUDY ON STUDENTSâ TRANSLATION OF AMY TANâS âTWO KINDSâ SHORT STORY - Kendenan, Esriaty S. (Language Circle: Journal of Language and Literature, 2017)
Similes and metaphors are two forms of figurative language which are very familiar in literary works.Â  One factor that arise some common problems faced by translators in translating simile and metaphor is the cultural difference between the source language and target language. Therefore, translators would apply certain strategies or procedures to find the equivalence of similes and metaphors in the target language.Â  In âTwo Kindsâ short story, it can be found that Amy Tan also uses several similes and metaphors.Â  For student translators in Literary Translation class, it is a challenge to translate similes and metaphors in âTwo Kindsâ into Indonesian. Thus, this research aims at describing how student translators of Literary Translation class deal with the translation of those similes and metaphors. Hopefully, this study would give worth contribution to the development of literary translation and particularly for student translators in translating any literary works. By comparing studentsâ translations and the source text, it is found that students mostly applied reproducing the same image in the TL procedure to translate similes and metaphors from English into Indonesian.